To assess the effectiveness of structured teaching programme by on pre and post test knowledge regarding prevention of chikungunya among adults (40-50 years) in selected rural areas - Nikam, Pooja (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: The aim of this study is to assess the pre test knowledge score regarding prevention of chikungunya among the adults and to assess the post test knowledge score regarding prevention of chikungunya among the adults. Methods: A quasi experimental design, pre and post test without control group was used for the present study to determine the effectiveness of structured teaching programme on knowledge regarding prevention of chikungunya among the adults (40-50 years) of selected rural areas of Maharashtra. The sample for the study consists of 60 adults (male & female) age group between 40-50 years in selected rural areas, Maharashtra. Results: Demographic variables such as education, drainage system and source of information were having significant association and demographic variables such as age, gender, religion, and occupation were not having significant association with pre test knowledge score. Highly significant difference found between the pre-test and post-test knowledge Scores at the level of (P<0.05). Majority of subject pre test having 31 (52%) poor knowledge score, 29 (48%) were average knowledge and 0 (0%) were good knowledge. Majority of subject post test having 38 (63.33%) average knowledge score, 17 (28.33%) were having good knowledge and 5 (8%) were having poor knowledge. Conclusion: The comparative study of about knowledge pre and post test teaching is finding suitable. The study reveals the positive outcome the importance of structured teaching programme and noted that the significant difference between knowledge regarding prevention of chikungunya among the adults (40-50 years) of selected rural areas of Maharashtra in pre and post test.